Design of the 590 MeV proton beamline for the proposed TATTOOS isotope production target at PSI. Issue 1 (1st January 2023) - Hartmann, M; Kiselev, D; Reggiani, D; Snuverink, J; Zhang, H; Seidel, M
Abstract: IMPACT (Isotope and Muon Production with Advanced Cyclotron and Target Technologies) is a proposed initiative envisaged for the high-intensity proton accelerator facility (HIPA) at the Paul Scherrer Institute (PSI). As part of IMPACT, a radioisotope target station, TATTOOS (Targeted Alpha Tumour Therapy and Other Oncological Solutions) will allow the production of terbium radionuclides for therapeutic and diagnostic purposes. The proposed TATTOOS beamline and target will be located near the UCN (Ultra Cold Neutron source) target area, branching off from the main UCN beamline. In particular, the beamline is intended to operate at a beam intensity of 100 μA, requiring a continuous splitting of the main beam via an electrostatic splitter. Realistic beam loss simulations to verify safe operation have been performed and optimised using Beam Delivery Simulation (BDSIM), a Geant4 based tool enabling the simulation of beam transportation through magnets and particle passage through the accelerator. In this study, beam profiles, beam transmission and power deposits are generated and studied.